Elaboración del estudio de prefactibilidad para el montaje de un servicio de alquiler de bicicletas a través de una red de estaciones en Bogotá. (2017)
This work is a Prefeasibility Study for the Assembly of a bicycle rental service through a stations network in Bogotá. It contains the Strategic Alignment, in which it was aligned to the goals of the District Department of Mobility, in this case to the program of Government of 2016-2020. It contains the marketing study, which holds information on existing supply and demand regarding how citizens get to one place to another in their daily lives, preferences, competition, places of greatest demand, etc. The environmental study includes the analysis of the feasibility of the project in relation to the environment and the repercussions that it could have with its daily operation. The administrative study, shows organization type, costs, legal requirements etc. The most viable location of the stations, taking into account factors of interconnectivity of bicycles roads, safety, etc. is defined in the technical study